Respuesta :

Answer:

(2,10)

Step-by-step explanation:

so we can substitute the y = 5x into y = 6x - 2

so we would have

5x = 6x - 2

subtract 6x from both sides

-x = -2

remove the negative signs since they're on both sides

x = 2

so now we can substitute x = 2 into y = 5x

so we would get

y = 5(2)

y = 10

So the point will be (2,10)

Check:

y = 6x - 2

10 = 6(2) - 2

10 = 12 - 12

10 = 10

y = 5x

10 = 5(2)

10 = 10

Answer:

(2, 10)

Step-by-step explanation:

substitute the given value of y into the equation (y=5x)

6x-2 =5x

solve for x

"add" the -2 to the other side to leave the x by itself on one side

6x=5x+2

"subtract" the 5x to the other side to combine the x's

6x-5x=2

collect like terms

x=2

so you now have your x to solve  for y

substitute the x into the equation (y=5x)

y=5(2)

simple

y=10

and there you have it!!

hope this helps!!!